Порівняльна характеристика стандарту Wi-Fi 802 Л lax - Греков, І. (ХНУРЕ, 2020)
A study was conducted of innovations in the new Wi-Fi standard 802 Л lax, and comparison was made of the main features and technologies with previous Wi-Fi standards 802ЛІП and 802.1 lac. Practical application was carried out on terminal devices that support this standard in order to record the performance of the new standard and indicators of connection speed.